(untitled) (Research, Society and Development, 2020)
Objective: to describe nursing interventions for the prevention of sexually transmitted infections during old age. Methodology: this is a bibliographic search typified as integrative review developed in the Bdenf, Lilacs and Medline databases accessed via the Virtual Health Library (VHL). The inclusion criteria were articles published in the last 5 years, theoretical methodological, qualitative and quantitative studies that addressed the topic of interest. Theses, monographs and dissertations were excluded. The descriptors used were: idoso, população idosa, pessoa idosa, aged, pacotes de assistência ao paciente, enfermagem, conjunto de cuidados, patient care bundles, doenças sexualmente transmissíveis, infecções sexualmente transmissíveis and sexually transmitted diseases, combined through the Boolean operators AND and OR. The sample was made up of nine articles. Results: most studies assessed were published on the Medline database, in 2017, with a descriptive and methodological design and the theme of interest focused on HIV/AIDS. The interventions took place through booklets, lectures, conversation circles, questionnaires, assessments, interviews and special attention. Conclusion: it was concluded that knowing the interventions is necessary, since they are successful practices that can be reproduced by other professionals in their clinical practice. Most interventions were the result of building light technologies for health education.